(176-(5x+35x))+(5x+35x)=176

Simple and best practice solution for (176-(5x+35x))+(5x+35x)=176 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (176-(5x+35x))+(5x+35x)=176 equation:


Simplifying
(176 + -1(5x + 35x)) + (5x + 35x) = 176

Combine like terms: 5x + 35x = 40x
(176 + -1(40x)) + (5x + 35x) = 176

Remove parenthesis around (40x)
(176 + -1 * 40x) + (5x + 35x) = 176

Multiply -1 * 40
(176 + -40x) + (5x + 35x) = 176

Remove parenthesis around (176 + -40x)
176 + -40x + (5x + 35x) = 176

Combine like terms: 5x + 35x = 40x
176 + -40x + (40x) = 176
176 + -40x + (40x) = 176

Combine like terms: -40x + (40x) = 0
176 + 0 = 176
176 = 176

Add '-176' to each side of the equation.
176 + -176 = 176 + -176

Combine like terms: 176 + -176 = 0
0 = 176 + -176

Combine like terms: 176 + -176 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 51.2/3 | | v^2+64= | | (176-(5x+35x))=10(176-(5x+35x)) | | 10q-4-4q=16 | | 7x^2-53x-21= | | -6n^2+7n+12=0 | | 0.9x-0.7x+0.3x=4 | | 18=-3(x-6) | | 19q-4-4q=-16 | | (38-(5x+35x))=10(38-(5x+35x)) | | 2l-7l=15 | | n^2+7n-72=0 | | 12a-6a= | | 5/7K=30 | | (2x+3)(x+4)(x-1)(x+3)=0 | | L/18=-10 | | 7(x-14)=-42 | | K/18--18 | | 4x-1-2x+2=3x-4x+-2 | | Kevin/18=-10 | | 20m^2-40=0 | | 1/3V=-6 | | 6/(k-2)=10 | | (38-(5x+35x))+(5x+35x)=38 | | ((5x^3)-(x)+(3))+((x^3)-(9x^2)+(4x))= | | (x+10)(x-4)=-24 | | 5*p+7-5*p-(-7*(p-3))= | | 3dx/dt-4x=sin2t | | ((5x+35x)-38)+(5x+35x)=38 | | -12x+8=-7x-2 | | (5x^3-x+3)+(x^3-9x^2+4x)= | | -3(6X+5)-2(1-17X)=3(1+5X) |

Equations solver categories